A companion to Margaret More Roper studies : life records, essential texts, and critical essays - Gentrup, William F., 1953-; McCutcheon, Elizabeth (Book collections on Project MUSE., 2022)
"This volume is an important contribution to the field of Margaret More Roper studies, early modern women's writing, as well as Erasmian piety, Renaissance humanism, and historical and cultural studies more generally. Margaret More Roper is the learned daughter of St. Thomas More, the Catholic martyr; their lives are closely linked to each other and to early sixteenth-century changes in politics and religion and the social upheaval and crises of conscience that they brought. Specifically, Roper's major works - her translation of Erasmus's commentary on the Lord's Prayer and the long dialogue letter between More and Roper on conscience - highlight two major preoccupations of the period: Erasmian humanism and More's last years, which led to his death and martyrdom. Roper was one of the most learned women of her time and a prototype of the woman writer in England, and this edited volume is a tribute to her life, writings, and place among early women authors. It combines comprehensive and convenient joining of biographical, textual, historical, and critical components within a single volume for the modern reader. There is no comparable study in print, and it fills a significant gap in studies of early modern women writers"--